Urological Injuries in Obstetrics and Gynaecological Surgery - M. Afzal; Nargis Iqbal (Journal of Rawalpindi Medical College, 2015)
Background: To determine the frequency of urinary tract injury during Obstetrics and Gynaecological surgery in the tertiary care teaching set up. Methods: In this descriptive study, all the patients who were admitted for obstetrical and gynaecological surgery irrespective of the time of procedure and level of surgical expertise were evaluated. Forty seven patients with bladder injury and six patients with ureteric injury were included. Site of injury, type and nature of surgical procedure, and therapeutic success rate with respect to time of diagnosis and treatment was analyzed. Injury was defined as entry into the urinary tract lumen, crushing, ligation or/and excision of urinary tract, leakage of urine, post operative hydronephrosis, or extravasation of contrast outside the urinary tract with or without renal damage that required surgical intervention. Results: The injury incidence in obstetrics emergency and elective procedures was 0.69% with urinary bladder the most frequently injured organ (88.67%). No ureteric injury was recorded in obstetrical patients. In gynaecological patients ratio of injuries to bladder and ureter was 4.84%. Most of the ureteric injuries (50%) were encountered in emergency laparotomy, followed by malignant ovarian tumours (33.3%). Most of the injuries were picked and dealt during the same surgical session with 15% of the patients requiring reoperation. Outcome of the management was satisfactory with no renal damage and mortality. Conclusion: Good knowledge of pelvic anatomy and practicing the visualization of ureteric course in routine patients will be helpful to safeguard it during complicated cases.